MINAT WIRAUSAHA KAUM SANTRI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI PADA PONDOK PESANTREN AR-RIYADH PALEMBANG) - Nadhira Ulfa, Nadhira Ulfa Nadhira Ulfa (Islamic Economics Program, Faculty of Islamic Economics and Business, 2015)
The aims of this research are to explore and analyze the factors that was effected the entrepreneurship intention of the senior students of islamic boarding school Ar-Riyadh Palembang. Nowdays the senior students of islamic boarding school of Ar-Riyadh and his alumni has begun to abondan the intention of entrepreneurship as it leads to developing his social economics matters. Using quantitative procedures, this research finds out that parsially t test shows t-valued 7,171 > than t-table 1,665. And simultaneously f test shows f-valued 88,136 > than v-table 3,97. From above findings, this reseach could explined that the entrepreneurship intentions of senior students of Ar-Riyadh Palembang has high category it had been reach 96,2 %. Internal and exsternal factors was significanlty effected his entrepreneurship intentions. Key Words:Entrepreneurship, Intentions, Senior Students, and Islamic Boarding School